2023
DOI: 10.1186/s13063-023-07422-w
|View full text |Cite
|
Sign up to set email alerts
|

Global posture reeducation compared with segmental muscle stretching exercises in the treatment of fibromyalgia: a randomized controlled trial

Luciana Akemi Matsutani,
Adriana de Sousa do Espírito Santo,
Marina Ciscato
et al.

Abstract: Background Muscle stretching exercises preserve corporal flexibility and decrease the retraction and shortening of myofascial and articular structures. These exercises are recommended for the treatment of fibromyalgia (FM). The purpose of the study was to verify and compare the effect of muscle stretching exercises on FM patients based on the global posture reeducation method against segmental muscle stretching exercises, both used in concert with an educational approach rooted in cognitive beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…[ 15 ] The evidence-based exercise and physical therapy are the cornerstones of FM treatment. [ 15 16 ] In our analysis, only a few proportions reported that patients suspected FM should be referred to a multi-disciplinary team, and few proportions recommended exercise (9.5%), education (7.4%), and behavioral therapy (2.9%). A previous Saudi study conducted on medical practitioners showed that physiotherapy was the major reported treatment for FM (37%), followed by medications (34%), whereas steroid/LA injections represented the least reported treatment (11%).…”
Section: Discussionmentioning
confidence: 85%
“…[ 15 ] The evidence-based exercise and physical therapy are the cornerstones of FM treatment. [ 15 16 ] In our analysis, only a few proportions reported that patients suspected FM should be referred to a multi-disciplinary team, and few proportions recommended exercise (9.5%), education (7.4%), and behavioral therapy (2.9%). A previous Saudi study conducted on medical practitioners showed that physiotherapy was the major reported treatment for FM (37%), followed by medications (34%), whereas steroid/LA injections represented the least reported treatment (11%).…”
Section: Discussionmentioning
confidence: 85%